Analysis of Syntax Errors in Written Language of 8th Grade Students with Hearing Impairment - Alvi, Iram Batool; Abdul Hameed (JIE, 2023)
Children with hearing loss confront a diversity of developmental challenges in the areas of language and literacy. This research studied ‘Syntactical Error Analysis’ in the written Urdu language of students with hearing impairment of 8th grade. The sample of the study consisted on the conveniently selected 100 students of 8th grade with hearing impairment studying in public and private institutions of Lahore and Sahiwal divisions. A self-developed writing test, consisting three open-ended questions was used to collect data. Data obtained were organized, tabulated and analyzed by using SPSS. Besides calculating the frequency distributions of demographic variables, descriptive statistics were used for data analysis. The analyses include mean, standard deviation, minimum and maximum value. Inferential statistical analyses e.g. independent sample t-test and analysis of variance (ANOVA) were used to compare errors of students on different institutions. On the basis of analysis, it is found that the majority of the respondents committed Syntactic Omission Errors whereas the Syntactic Addition Errors and Syntactic Substitution Errors are highly related with each other. Committing Syntax errors in written language is not affected by the gender of respondents and divisional difference, but on the basis of institutions.